Are Scholars Better Bloggers? Bloggership: How Blogs Are Transforming Legal Scholarship - Paul L. Caron (Washington University Law Review, 2006)
A perennial debate in higher education in general, and in legal education in particular, is whether a robust scholarly life helps or hurts a professor’s teaching performance. Taking inspiration from panelist Jim Lindgren’s work, Are Scholars Better Teachers?, which concludes that better scholars are perceived by students to be better teachers, Caron asks a panel, “Are Scholars Better Bloggers?” These comments explore both scholarship and blogging data to begin to answer that question.
Keywords: Blogs; Law – Study & amp; teaching